2012
DOI: 10.1371/journal.pone.0039451
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomics of Inner Membrane Fraction from Carbapenem-Resistant Acinetobacter baumannii with a Reference Strain

Abstract: Acinetobacter baumannii has been identified by the Infectious Diseases Society of America as one of the six pathogens that cause majority of hospital infections. Increased resistance of A. baumannii even to the latest generation of β-lactams like carbapenem is an immediate threat to mankind. As inner-membrane fraction plays a significant role in survival of A. baumannii, we investigated the inner-membrane fraction proteome of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 54 publications
1
68
0
Order By: Relevance
“…Carbapenem resistant A. baumannii has been already studied using outer membrane proteomics between wild type and resistance strain [108,[140][141][142]. Membrane proteomics result also showed that A. baumannii displays a vigorous and adaptable metabolism [143,144].…”
Section: Significance Of Omv Proteomics In the Study Of Drug Resistanmentioning
confidence: 99%
“…Carbapenem resistant A. baumannii has been already studied using outer membrane proteomics between wild type and resistance strain [108,[140][141][142]. Membrane proteomics result also showed that A. baumannii displays a vigorous and adaptable metabolism [143,144].…”
Section: Significance Of Omv Proteomics In the Study Of Drug Resistanmentioning
confidence: 99%
“…Acinetobacter baumannii has emerged over several decades as a problematic human pathogen, the major cause of healthcare-associated infections including bacteremia, pneumonia, meningitis, urinary tract infection, and wound infection [38,39]. The carbapenems are a class of β-lactam antibiotics most commonly prescribed to treat infection, but A. baumannii has developed resistance leading to significant health [38].…”
Section: Stress Responses In Prokaryotic Microorganismsmentioning
confidence: 99%
“…The carbapenems are a class of β-lactam antibiotics most commonly prescribed to treat infection, but A. baumannii has developed resistance leading to significant health [38]. Proteomic analysis of the inner-membrane fraction of a carbapenem-resistant strain of A. baumannii, using differential in-gel electrophoresis (DIGE) with DeCyder, Progenesis and LC-MS/MS, identified 19 over-expressed and 4 down-regulated proteins in the resistant strain (RS307) compared to the reference (ATCC 19606) [39]. Proteins up-regulated in the resistant strain are associated with β-lactamase, protein synthesis and chaperonins, seven of which have a role in metabolism and energy production.…”
Section: Stress Responses In Prokaryotic Microorganismsmentioning
confidence: 99%
“…β-lactams inhibit the membrane synthesis and therefore kill bacteria. In order to escape the action of β-lactams, A. baumannii primarily utilizes production of β-lactamases, enzymes which cleave the β-lactam ring (Garau et al, 2005;Kohlenberg et al, 2009;Peleg et al, 2008;Tiwari, et al, 2012a;Tiwari et al, 2012b;Walsh, Toleman, Poirel, & Nordmann, 2005). Catalytic degradation of β-lactam by β-lactamase involves the formation of transient complex (β-lactamase-β-lactam) which subsequently releases hydrolyzed β-lactam.…”
Section: Introductionmentioning
confidence: 99%